Penerapan Keselamatan Dan Kesehatan Kerja Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Moderating - Sitompul, Robin Hood; Ni Bulan, Tapi Rondang; Setiawan, Teguh (JaManKu: Jurnal Manajemen dan Kewirausahaan, 2024)
This study aims to determine the application of occupational safety arid health to employee performance partially and with job satisfaction as a moderating variable at PT PLN (Persero) North Sumatra Generation Main Unit Associative research design with a quantitative approach. The population of this study was 155 people, the sampling technique was using the Slovin formula as many as 112 respondents with probability sampling, namely random sampling The analysis technique used is simple linear regression and MRA.Based on the results of the research conducted, it shows that the variables of the application of occupational safety and health have a positive and significant effect on employee performance variables, Job satisfaction does not prove significant in moderating the variables of the application of occupational safety and health to employee performance variables.